2019
DOI: 10.3390/ani9100784
|View full text |Cite
|
Sign up to set email alerts
|

Nitroethanol in Comparison with Monensin Exhibits Greater Feed Efficiency Through Inhibiting Rumen Methanogenesis More Efficiently and Persistently in Feedlotting Lambs

Abstract: Simple SummaryThis study aimed to determine dietary supplemental effects of nitroethanol (NEOH) in comparison with monensin on growth performance, nutrient digestibility, rumen fermentation characteristics and methane production in feedlotting lambs. The dietary addition of NEOH in comparison with monensin presented a greater promoting effect on growth performance in feedlotting lambs by inhibiting methanogenesis more efficiently and persistently in the rumen. Although dietary NEOH or monensin addition did not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…Although NEOH is considered an efficient ruminal CH 4 inhibitor in vitro [ 29 , 30 ], little information is available regarding its nutritive and feeding value as livestock feed. Only in a recent study of Zhang et al [ 18 ], the supplementation of NEOH had no adverse influence on the apparent digestibility of nutrient. The DMI was decreased with monensin addition in the current study.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Although NEOH is considered an efficient ruminal CH 4 inhibitor in vitro [ 29 , 30 ], little information is available regarding its nutritive and feeding value as livestock feed. Only in a recent study of Zhang et al [ 18 ], the supplementation of NEOH had no adverse influence on the apparent digestibility of nutrient. The DMI was decreased with monensin addition in the current study.…”
Section: Discussionmentioning
confidence: 93%
“…Dietary monensin addition often has an ability to decrease rumen motility and dilution rate of digestion of nutrients, resulting in an increase of ruminal fill and consequently a reduction of DMI. Dietary supplementation of NEOH has recently been discovered to have a negative effect on DMI in fattening lambs [ 18 ]. Furthermore, in agreement with this study, the DMI was similarly decreased with NEOH addition in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, nitrocompounds act like monensin, in terms of both inhibiting methane production and suppressing parasite colonization in ruminants and chickens [ 23 , 30 , 31 , 32 , 33 , 34 , 35 ]. Teng et al [ 32 ] demonstrated that 0.5 mg/mL of monensin and 0.5 mM 2NPOH and 2NEOH significantly inhibited development of sporozoites in the Madin-Darby bovine kidney cells.…”
Section: Inhibition Of Eimeria Sppmentioning
confidence: 99%